Pengaruh Harga Komoditas, Kurs, Inflasi, Foreign Direct Investment (FDI), Dan Sumber Daya Manusia (SDM) Terhadap Perekonomian Negara OKI - Evi Aninatin Ni'matul Choiriyah, - (Departemen Ekonomi Syariah, FEB, Universitas Airlangga, 2020)
This study aims to determine the effect of world commodity prices on agriculture, energy, fertilizer, metals and minerals, precious metals, inflation, exchange rate of the United States Dollar (USD), Foreign Direct Investment, human resources on economics of Organization of Islamic Cooperation (OIC) which is proxied in Gross Domestic Product (GDP) in the 2009-2018 period. In this study, there are two models regarding the human resources variable, namely total population and labor force. Random Effect Model (REM) is used in this study to examine the relationship of independent variables to the dependent variable, both partially and simultaneously. The findings of this study, both the first and second models show that commodity prices in the agriculture, fertilizer, metal and mineral sectors, Foreign Direct Investment, and inflation have a negative and significant effect on the GDP of the OIC countries. Meanwhile, commodity prices in the energy sector, precious metals, and the exchange rate of the United States Dollar (USD) have a positive and significant effect on the GDP of the OIC countries. As well as the human resources variable, both the population and the labor force also have a positive and significant effect on the GDP of the OIC countries. This paper can be considered for the government or related institutions and agencies in formulating policies or regulations to improve and maintain economic stability in each OIC member country.